1995
DOI: 10.1007/bf01957503
|View full text |Cite
|
Sign up to set email alerts
|

Serology toBartonella (Rochalimaea) henselae may replace traditional diagnostic criteria for cat-scratch disease

Abstract: Bartonella (Rochalimaea) henselae has been identified as causative agent of cat-scratch disease (CSD). Employing an indirect fluorescence antibody test we found that 20 (100%) out of 20 children with suspected CSD had serum titres to B. henselae of > or = 512. By contrast, in all but one of the controls (n = 332) including subjects exposed to the same cats, patients with diseases other than CSD, and blood donors the antibody titres were < or = 256 (P < 0.001). However, significant regional differences in serop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 12 publications
7
36
0
1
Order By: Relevance
“…The cutoff titer may depend on the seroprevalence of antibodies to Bartonella spp. in the population, and this may vary with geographical region (45,48,55,65). We found a specificity of 98.8% with the in-house test but only 87% with the FT test for the 85 controls we studied.…”
Section: Discussionmentioning
confidence: 54%
“…The cutoff titer may depend on the seroprevalence of antibodies to Bartonella spp. in the population, and this may vary with geographical region (45,48,55,65). We found a specificity of 98.8% with the in-house test but only 87% with the FT test for the 85 controls we studied.…”
Section: Discussionmentioning
confidence: 54%
“…The positive rates to the organism in CSD individuals varied from 6.3% (26/412) in Italy (4) to 100% (20/20) in Switzerland (12). A higher seropositive rate against B. henselae in CSD-suspected patients in Japan indicated that B. henselae was also a major causative agent of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The role of B. henselae as the major causative agent of CSD has been based on serological survey [23], culture [18], and detection by PCR-based molecular techniques [3±5, 7, 12, 27] from clinical specimens of patients with CSD. Currently the laboratory diagnosis of CSD is based on serology [9,21,23] and PCR-based assays [3±5, 7, 12, 27] due to the diculty to establish a gold standard. Although serology is characterized by a cross-reactivity with other Bartonella species [17], nevertheless it might be considered the method of choice in CSD diagnosis [13,21].…”
Section: Discussionmentioning
confidence: 99%
“…Currently the laboratory diagnosis of CSD is based on serology [9,21,23] and PCR-based assays [3±5, 7, 12, 27] due to the diculty to establish a gold standard. Although serology is characterized by a cross-reactivity with other Bartonella species [17], nevertheless it might be considered the method of choice in CSD diagnosis [13,21]. However, either in atypical cases of CSD or when serology results are not yet positive or inconclusive, PCR-based assays can replace the serological studies.…”
Section: Discussionmentioning
confidence: 99%